GPS数据采集技术及其在海洋调查中的应用 - 邱雨生; 陈敏; 刘广山 (2003)
本文应用VB6.0开发了智能化的GPS数据采集软件.对该软件的功能进行了简单的介绍,同时对一些关键技术作了较详细的描述.利用该软件、GPS接收机及PC机的组合,可对走航式测量仪器(或移动设备)进行实时定位并保存定位记录,且大大减少一些不必要的数据,使得软件更为实用. Considering the difficulty of GPS data processing in the 16th Chinese National Antarctic Research Expedition (CHINARE). A GPS data processing program was developed using Visual Basic 6.0. In this paper, the function and the key technique of this program was introduced. It is possible to determine the location of the shipboard or insitu detectors/instruments exactly and to obtain the digital record for measured parameters. This program was further optimized by reducing nonnecessary GPS data during shipboard measurements. 国家自然科学基金资助项目(49836010).